Do low dose CT-KUBs really expose patients to more radiation than plain abdominal radiographs?. Issue 4 (November 2021) - Yang, Bob; Suhail, Noorunisa; Marais, Johan; Brewin, James
Background: Urolithiasis patients often require frequent urinary tract imaging, leading to high radiation exposure. CT Kidney-Ureter-Bladder (CT-KUB) is the gold standard in urolithiasis detection, however it is thought to harbour significant radiation load. Urologists have therefore utilised abdominal radiographs (XR-KUB) as an alternative, though with markedly lower sensitivity and specificity. We present the first contemporary UK study comparing the effective doses of XR-KUBs with low dose CT-KUBs. Method: Fifty-three patients were retrospectively identified in a single centre who underwent both a XR-KUB and a CT-KUB in 2018. Effective-Dose was measured by converting the recorded 'Dose Area/Length Product' via the International Commission on Radiological Protection formula. Results: The average effective dose of XR-KUBs and low dose CT-KUBs were 5.10 mSv and 5.31 mSv respectively. Thirty-four percent (18/53) of patients had a XR-KUBs with a higher effective dose than their low dose CT-KUB. Patients with higher Weight, BMI and AP diameter had higher effective doses for both their XR and low dose CT-KUBs. All patients in our study weighing over 92 kg or with a BMI greater than 32 had a XR-KUBs with a higher effective dose than their low dose CT-KUB. Conclusion: This data supports moving away from XR-KUBs for the investigation of urolithiasis, particularly in patients with a high BMI.